O Carmen Sacrum de Proba (Nuntius Antiquus, 2010)
The Carmen Sacrum of Proba, a Roman aristocrat christianized in the fourth century, intends to evangelize, according to the concepts of orthodox soteriology, and is also based on metric juxtapositions of fragments from the works of Virgil. Here, we describe both aspects of this curious work.